2017
DOI: 10.3389/fphys.2017.00379
|View full text |Cite
|
Sign up to set email alerts
|

Human Peritoneal Mesothelial Cell Death Induced by High-Glucose Hypertonic Solution Involves Ca2+ and Na+ Ions and Oxidative Stress with the Participation of PKC/NOX2 and PI3K/Akt Pathways

Abstract: Chronic peritoneal dialysis (PD) therapy is equally efficient as hemodialysis while providing greater patient comfort and mobility. Therefore, PD is the treatment of choice for several types of renal patients. During PD, a high-glucose hyperosmotic (HGH) solution is administered into the peritoneal cavity to generate an osmotic gradient that promotes water and solutes transport from peritoneal blood to the dialysis solution. Unfortunately, PD has been associated with a loss of peritoneal viability and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 94 publications
(151 reference statements)
0
10
0
Order By: Relevance
“…Early ROS production depends on TLR4, Nox2 and Nox4 and, is suggested to be mediated by PLC/cPKC and PI3-K pathways [ 169 ]. Interestingly, TRPM4 is a Ca 2+ -activated channel [ 171 ] and early ROS production is preceded by Ca 2+ influx [ 172 ]. The origin of the intracellular Ca 2+ increase prompting these pathways remains elusive.…”
Section: Trp Channels Are Sensors Of Bacterial Endotoxinsmentioning
confidence: 99%
“…Early ROS production depends on TLR4, Nox2 and Nox4 and, is suggested to be mediated by PLC/cPKC and PI3-K pathways [ 169 ]. Interestingly, TRPM4 is a Ca 2+ -activated channel [ 171 ] and early ROS production is preceded by Ca 2+ influx [ 172 ]. The origin of the intracellular Ca 2+ increase prompting these pathways remains elusive.…”
Section: Trp Channels Are Sensors Of Bacterial Endotoxinsmentioning
confidence: 99%
“…In fact, the presence of free radicals in the effluent is associated with technique failure in stable PD patients [ 13 , 14 ]. Previous studies have demonstrated that glucose-rich and/or acidic hypertonic PD solutions could be associated with higher levels of oxidative stress [ 15 , 16 , 17 , 18 ]. The PD-related oxidative process can be modulated by drug treatments used in these patients [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In light of our main findings, the following points briefly clarify our hypothesis. First, the destruction of peritoneal mesothelial cells has been reported in previous studies, and in particular, it has found to be higher after exposure to 4.2% dextrose [ 3 , 25 ]. Kang et al [ 26 ] found that various incremental ranges in glucose concentrations, including 30, 60, and 90 mmol/L, caused 2.3-, 3.6-, and 4.0-fold increases in the induced fibrosis factor, respectively.…”
Section: Discussionmentioning
confidence: 86%